Mengulik Kiat Gereja Dalam Menyiapkan Generasi Muda Matang Secara Finansial: Sebuah Pembelajaran Penting Dari Kisah Hidup Yusuf - Hutapea, Sophia Maranatha; Hastuti, Ruwi (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2025)
The church has an important role in preparing its young generation to be financially mature because this will have an impact on preventing the young generation from becoming a burden on their families, increasing their opportunities to contribute more to society, and socio-economically, the church's next generation will of course be of higher quality. This article aims to explore the church in preparing its young generation to be financially mature, referring to important lessons from Joseph's life story. The method used in this research is descriptive qualitative and literature review. This article highlights the importance of the younger generation being financially prepared, important lessons for managing finances from Joseph's life story, and the church strategies in preparing young people to be financially mature. It was concluded that the church will be optimal in preparing its young generation to be financially mature when teaching modeling of financial use, increasing financial training seminars, developing a culture of saving, and educating its young generation to invest.AbstrakGereja memiliki peran penting untuk mempersiapkan generasi mudanya matang secara finansial, tentunya hal ini akan berdampak pada menghindarkan generasi muda tersebut menjadi beban bagi keluarganya, memperbesar peluang mereka untuk lebih berkontribusi di masyarakat, dan secara sosial ekonomi pun generasi penerus gereja akan lebih berkualitas. Artikel ini bermaksud mengulik kiat gereja dalam menyiapkan generasi mudanya matang secara finansial merujuk pada pembelajaran penting dari kisah hidup Yusuf. Metode yang digunakan dari penelitian ini adalah deskriptif kualitatif dan kajian literatur. Artikel ini menyoroti pentingnya generasi muda dipersiapkan secara finansial, berbagai pembelajaran penting mengelola keuangan dari kisah hidup Yusuf, serta kiat gereja dalam mempersiapkan anak mudanya yang matang secara finansial. Disimpulkan bahwa gereja akan maksimal dalam menyiapkan generasi mudanya matang secara finansial ketika mengajarkan modeling penggunaan keuangan, memperbanyak seminar pelatihan finansial, mengembangkan budaya menabung, dan mendidik gererasi mudanya untuk berinvestasi.